A BIBLIOMETRIC ANALYSIS ON CULTURAL ECOSYSTEM SERVICES ASSESSMENT STUDIES: TRENDS, INSIGHTS AND FUTURE IN A DECADE - Mohd Nasir, Nurul Akmaniza; Hj Baharuddin, Zainul Mukrim (Journal of Architecture, Planning and Construction Management, 2025)
Cultural ecosystem services (CES) refer to intangible benefits derived from human interactions with their surrounding environment, such as recreational opportunities, aesthetic value, cultural heritage, and spiritual value. While attention is increasing towards CES, the growing fragmentation of methodologies, varied geographical distribution, and the lack of standardised assessment remain significant challenges for its integration into urban planning strategies. This paper aims to analyse global research trends in CES assessment and valuation between 2015 and 2025 and to formulate the future direction of CES assessment studies to enhance human-environment interaction. This study employed bibliometric analysis using BiblioMagika and VOSviewer to visualise the recent trends and patterns in CES assessment studies, based on a review of 173 journals from the Scopus database. The findings reveal that CES studies have received considerable academic attention over the decade, especially after 2020, and have mostly come from developed countries such as Germany and the United States, and more recently from China. However, regions with rich biodiversity are still underrepresented, such as Southeast Asia countries. Key themes include social media analysis, participatory spatial mapping, urban green space, and urban green infrastructure, which show their credibility in shifting the world’s attention towards urban sustainability.